THE IMPACT OF LOAN VOCABULARY ON THE EXISTENCE OF INDONESIAN AS AN OFFICIAL LANGUAGE - Rina Devianty; Mhd. Alfin Rangkuti (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2026)
Indonesian language as the official language of NKRI faces challenges from foreign language loanwords, especially Mandarin and English. This study analyzes the impact of loanwords on the existence of Indonesian as an official language. Using a qualitative descriptive method, data were collected from relevant literature and language policies. Results show that loanwords can affect the uniqueness and function of Indonesian if not managed properly. Uncontrolled loanwords can reduce language authenticity, affect learning processes, and threaten national linguistic identity. Effective loanword management strategies, such as adaptation and standardization, are needed to maintain Indonesian's existence as an official language and strengthen national identity.